Challenges in Image-Guided Drainage of Infected Pleural Collections: A Review - Ashu S. Bhalla; Manisha Jana; Priyanka Naranje; Swish K. Singh; Irshad Banday (Journal of Clinical Interventional Radiology ISVIR)
Infected pleural fluid collections (IPFCs) commonly occur as a part of bacterial, fungal, or tubercular pneumonia or due to involvement of pleura through hematogenous route. Management requires early initiation of therapeutic drugs, as well as complete drainage of the fluid, to relieve patients' symptoms and prevent pleural fibrosis. Image-guided drainage plays an important role in achieving these goals and improving outcomes. Intrapleural fibrinolytic therapy (IPFT) is also a vital component of the management. The concepts of image-guided drainage procedures, IPFT, and nonexpanding lung are discussed in this review.